2019
DOI: 10.1007/s00784-019-02886-0
|View full text |Cite
|
Sign up to set email alerts
|

Association of oral mucosa hyperpigmentation with imatinib mesylate use: a cross-sectional study and a systematic literature review

Abstract: Objectives To assess the association between oral mucosa hyperpigmentation in patients with leukemia and imatinib mesylate use. Additionally, we compared our data to those obtained from a systematic review. Materials and methods A cross-sectional study was conducted with 74 patients undergoing treatment with imatinib mesylate. Sociodemographic characteristics, oral mucosa alterations, and medical history were evaluated. Oral hyperpigmentation was scored. The use of imatinib mesylate and hydroxyurea was evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 60 publications
0
9
0
Order By: Relevance
“…Included cohort studies achieved a moderate level of quality, 5 , 11 , 28 , 40 , 60 while the cross-sectional study achieved a high level of quality. 39 , 59 The quality of each included study is summarized in Supplementary Table 2–4 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Included cohort studies achieved a moderate level of quality, 5 , 11 , 28 , 40 , 60 while the cross-sectional study achieved a high level of quality. 39 , 59 The quality of each included study is summarized in Supplementary Table 2–4 .…”
Section: Resultsmentioning
confidence: 99%
“…Imatinib-associated hyperpigmentation was described by several studies that reported treatment duration as a major risk factor leading to larger and darker lesions. 59 , 68 , 69 In addition, antimalarial was the second most common category caused MIOH. A long duration (up to 15 years) of use of antimalarial drugs was observed to be associated with severe blue-black and gray diffused lesions in the hard palate with cutaneous involvement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the exact duration of use and dosage of both drugs were not determined in the study. 14 Our literature search revealed only nine reports of HUassociated oral pigmentation (four female patients and five male patients; eight adults and one child). 9,[15][16][17][18][19][20][21][22] The age of the affected individuals ranged between 10 and 68 years (mean, 50.6 years of age).…”
Section: Discussionmentioning
confidence: 97%
“…The results of this cross‐sectional study supported that hyperpigmentation extent and intensity were related to IM use especially when combined with HU. However, the exact duration of use and dosage of both drugs were not determined in the study 14 …”
Section: Discussionmentioning
confidence: 99%